Evaluación del cambio de sistema de levantamiento artificial de bombeo electrosumergible a bombeo hidráulico para la optimización energética en un campo petrolero (2019)
It seeks to identify the injection lines that lead to clusters with at least one active injector well, where a preselection of the producing wells candidate for the change of ALS is carried out according to the characteristics of the production fluid at surface and the IPR curve developed from real data of the field, verifying the values of these aspects in a matrix. Subsequently, a nodal analysis is performed to recognize the pressures handled in each of the systems, determining a Hydraulic Pumping design that allows the simulation of its operation compared to the currently implemented (ESP) further to obtaining the energy information consumed by both. Thus, it is possible to determine the prospective wells to change its ALS, and performing an economic analysis for its implementation. The previously described procedure is performed using Excel and the software given by the company.